The Influence of Online Learning on the Development of Students at SD Muhammadiyah 5 Porong During the Covid Pandemic - May Lucyana Kartono Putri; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The COVID-19 pandemic has disrupted the online learning process. So a solution is needed to answer these problems. Online learning can solve this problem. The purpose of this study was to obtain an overview of online implementation at Muhammadiyah 5 Porong Elementary School. The research method used the interview method by asking questions to 1 respondent. Based on the data it was found that all students did online learning and it was carried out according to their respective lesson schedules. The material information obtained through online learning is not effective for elementary school age children. The media used during online learning and the majority use the Google Classroom and Google Meet systems. Although this system can be used as a solution for conditions during the COVID-19 pandemic, several obstacles such as unstable internet networks, limited quotas, and others. In conditions of an outbreak Covid-19, online learning can be used with consideration of students' conditions, so they will get used to adjusting to the online system, learning can be done well. In addition, this online system can be used additional experiences for students in the future.The positive influence can be done anywhere and anytime according to the existing conditions. Because more time is spent at home, online learning can also increase the closeness between students and their parents. The negative influence of students who complain about the ineffectiveness of online learning, such as too many assignments, different internet networks for each student, difficulty understanding the material provided by the teacher, students also get bored quickly, and many others.